Metal-based nanoparticles, sensors, and their multifaceted application in food packaging - Antul Kumar; Anuj Choudhary; Harmanjot Kaur; Sahil Mehta; Azamal Husen (Journal of Nanobiotechnology, 2021)
Abstract Due to the global rise of the human population, one of the top-most challenges for poor and developing nations is to use the food produces safely and sustainably. In this regard, the storage of surplus food (and derived products) without loss of freshness, nutrient stability, shelf life, and their parallel efficient utilization will surely boost the food production sector. One of the best technologies that have emerged within the last twenty years with applications in the packaging of food and industrial materials is the use of green mode-based synthesized nanoparticles (NPs). These NPs are stable, advantageous as well as eco-friendly. Over the several years, numerous publications have confirmed that these NPs exert antibacterial, antioxidant, and antifungal activity against a plethora of pathogens. The storage in metal-based NPs (M-NPs) does not hamper the food properties and packaging efficiency. Additionally, these M-NPs help in the improvement of properties including freshness indicators, mechanical properties, antibacterial and water vapor permeability during food packaging. As a result, the nano-technological application facilitates a simple, alternate, interactive as well as reliable technology. It even provides positive feedback to food industries and packaging markets. Taken together, the current review paper is an attempt to highlight the M-NPs for prominent applications of antimicrobial properties, nanosensors, and food packaging of food items. Additionally, some comparative reports associated with M-NPs mechanism of action, risks, toxicity, and overall future perspectives have also been made.